ATTESTATION OF E-LEARNING COURSES IN DISTANCE LEARNING SYSTEM (Journal of Information Technologies in Education (ITE), 2010)
The article considered the procedure for certification of courses that are developed based distance learning platform, the analysis of basic legal documents devoted to this issue and the procedure for holding such certification.
Keywords: certification; criteria of quality; distance learning platform; eLearning; electronic resource